Development of a Smart Air Pollution Detection System Utilizing MQ2 Sensor and Node MCU ESP8266 with Telegram Integration - Agus Alim; Almamalik Lukmanulhakim; W, Chairunnisa (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
The rapid increase in air pollution, particularly in indoor environments, poses significant health risks. This study aims to develop a smart air pollution detection system using the MQ2 gas sensor integrated with the NodeMCU ESP8266 microcontroller and Telegram messaging application for real-time monitoring and notification. The system is designed to detect harmful pollutants, specifically cigarette smoke, and notify users when pollution levels exceed 100 parts per million (PPM). The MQ2 sensor measures the concentration of gases, while NodeMCU ESP8266 processes the data and communicates with the Telegram API to send alerts. The system was tested at the Banjaran District Office, where it demonstrated high accuracy in detecting indoor air pollution, with a response time of approximately 2 seconds and an alert accuracy of 100%. The results show that the system provides an effective and affordable solution for real-time air quality monitoring, contributing to improved indoor environmental health. Future enhancements could include expanding the system's detection capabilities to monitor additional pollutants and integrating it into larger IoT-based environmental systems.